The Effect of Using Taylor Swift’s Songs on the Improvement of Students’ Listening Skills at SMA Negeri 1 Loa Janan - Indah Cahyani; Ade Ismail Ramadhan Hamid; Abdul Halim (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study investigates the effect of using Taylor Swift’s songs on improving students’ selective listening skills at SMA Negeri 1 Loa Janan. Selective listening refers to learners’ ability to identify specific information, keywords, and main ideas from spoken texts. Songs were chosen as learning media because they provide authentic pronunciation, natural rhythm, and meaningful repetition that support focused listening practice. The study employed a pre-experimental one-group pretest–posttest design involving 32 tenth-grade students. Data were collected using a listening test consisting of ten fill-in-the-blank questions based on selected Taylor Swift songs. The test measured students’ ability to recognize keywords and accurately complete missing words and phrases from the song lyrics. The instrument was reviewed by English teachers to ensure content relevance and clarity. The treatment was conducted over four instructional sessions using structured listening activities, including lyric prediction, gap-filling, and comprehension checks. The results showed a significant improvement in students’ selective listening performance after the treatment. The mean posttest score was higher than the pretest score, and statistical analysis using a paired-sample t-test indicated a significant difference at the 0.05 level. These findings suggest that integrating English songs into listening instruction can effectively support students’ ability to focus on specific auditory information and improve listening accuracy. This study offers practical implications for English teachers to use music-based activities as supplementary listening materials to enhance learner engagement and selective listening development in secondary school contexts.